Bridging Financial Barrier: A Development Of Hybrid Takaful Model Towards Quality Mental Health Care Services In Malaysia - Khairil Faizal Khairi; Nur Hidayah Laili; Hisham Sabri (Human Resource Management Academic Research Society, 2024)
Indexed by ERA/MYCITE